Novel and cross-amplified microsatellite loci for the critically endangered São Paulo marsh antwren Formicivora paludicola (Aves: Thamnophilidae) - Camargo, Crisley de [UNESP]; Costa, Mariellen C.; Del Rio, Glaucia C.; Gibbs, H. Lisle; Glenn, Travis C.; Bagal, Ujwal; Silveira, Luis F.; Wasko, Adriane P. [UNESP]; Francisco, Mercival R. (Springer, 2015)
The So Paulo marsh antwren (Formicivora paludicola) is a critically endangered bird endemic to marshes in the metropolitan region of So Paulo city, Brazil. The total population is estimated to be around 300 individuals, distributed among 15 small (< 50 ha) fragments, suggesting that loss of genetic variability may affect the long-term viability of this species. To develop genetic tools for gaining information on effective population sizes, inbreeding and gene flow between populations, we describe nine polymorphic microsatellite loci isolated from a F. paludicola library using next-generation sequencing. We report on levels of variation in these novel microsatellites and eight additional heterologous loci in these birds. Expected (H (E)) and observed (H (O)) heterozygosities averaged 0.72 and 0.70, respectively, and the number of alleles per locus ranged from 3 to 10. These loci will permit evaluation of whether artificial translocations are necessary for long-term viability of this rare bird.
Keywords: Passeriformes; Microsatellites; Next-generation sequencing; Conservation genetics